N‐of‐1 Trials for Closed‐Loop Deep Brain Stimulation Devices. Issue 2 (19th March 2020) - Stevens, Ian; Gilbert, Frederic
ABSTRACT: Closed‐loop deep brain stimulation (DBS) devices hold great promise for treating various neurological and psychiatric conditions. Yet while these algorithmic‐based devices provide personalized treatment to each patient, they also present uniquely individualized risks of physiological and psychological harms. These experimental devices are typically tested in randomized controlled trials, which may not be the optimum approach to identifying and assessing phenomenological harms they pose to patients. In this article, we contend that an N‐of‐1 trial design—which is being used ever more frequently to realize the goals of individualized, precision medicine—could provide beneficial phenomenological data about the potential risks of harm to properly inform the use of closed‐loop DBS devices. Data from N‐of‐1 trials may provide patients, as well as their families and other caregivers, with better information on which to base informed choices about pursuing this type of treatment option.